Colchicine Does Not Reduce Abdominal Aortic Aneurysm Growth in a Mouse Model - James Phie; Shivshankar Thanigaimani; Pacific Huynh; Raghuveeran Anbalagan; Corey S. Moran; Robert Kinobe; Joseph V. Moxon; Matt A. Field; Smriti M. Krishna; Jonathan Golledge (Cardiovascular Therapeutics)
Background and Aims. The nacht domain, leucine-rich repeat, and pyrin domain-containing protein 3 (NLRP3) inflammasome is upregulated in human abdominal aortic aneurysm (AAA), but its pathogenic role is unclear. The aims of this study were firstly to examine whether the inflammasome was upregulated in a mouse model of AAA and secondly to test whether the inflammasome inhibitor colchicine limited AAA growth. Methods. AAA was induced in eight-week-old male C57BL6/J mice with topical application of elastase to the infrarenal aorta and oral 3-aminopropionitrile (E-BAPN). For aim one, inflammasome activation, abdominal aortic diameter, and rupture were compared between mice with AAA and sham controls. For aim two, 3 weeks after AAA induction, mice were randomly allocated to receive colchicine (n=28, 0.2 mg/kg/d) or vehicle control (n=29). The primary outcome was the rate of maximum aortic diameter increase measured by ultrasound over 13 weeks. Results. There was upregulation of NLRP3 markers interleukin- (IL-) 1β (median, IQR; 15.67, 7.11-22.60 pg/mg protein versus 6.87, 4.54-11.60 pg/mg protein, p=.048) and caspase-1 (109, 83-155 relative luminosity units (RLU) versus 45, 38-65 RLU, p<.001) in AAA samples compared to controls. Aortic diameter increase over 80 days (mean difference, MD, 4.3 mm, 95% CI 3.3, 5.3, p<.001) was significantly greater in mice in which aneurysms were induced compared to sham controls. Colchicine did not significantly limit aortic diameter increase over 80 days (MD -0.1 mm, 95% CI -1.1, 0.86, p=.922). Conclusions. The inflammasome was activated in this mouse model of AAA; however, daily oral administration of colchicine did not limit AAA growth.